PENGARUH MINI HOME EDUCATION TERHADAP RASA INGIN TAHU ANAK USIA 4-5 TAHUN - Adjeng Tria Puspita (STKIP Subang, 2023)
This research is aimed at parents who have children aged 4-5 years in the village of Margatani, Kramatwatu sub-district. In this study researchers used data collection, a survey is a method used to collect information from a number of people in the form of opinions. Based on the results of data processing and data analysis, the results of research on